An International Comparison of Financial Consumer Protection (Springer Singapore, 2018)
This book explores consumer protection in the major financial markets in the world and provides an international comparison among the countries of different cultural background and economic development. Each chapter describes the major issues of financial consumption in the selected country and the efforts to counter the problems of financial consumption. The innovation and renovation in the financial institutions and the public policies for consumer protection are also analyzed for their potential impacts on the future development of financial markets.